Soal Tipe PISA : Konteks Peningkatan Kasus Covid-19 - Quratul Aini Febriyanti; Arvin Efriani; Atika Zahra; Feli Ramury (JEMST (Jurnal of Education in Mathematics, Science, and Technology), 2021)
This study aims to produce valid PISA type questions in the context of Covid-19. The method in this research is design research research method with the type of development studies or development research. This research data collection technique by means of documentation, video recordings, and interviews. This study involved 4 validators including 3 PISA expert validators and students researching PISA. The subjects of this study were students of class VIII SMP Negeri 21 Batam who were carried out online and using the Zoom application. This study resulted in six valid PISA type questions in the context of Covid-19 at levels 1 to 6. One of the questions developed was the increase in Covid-19 cases by calculating the increase in Covid-19 cases in Jakarta Province. Based on the results of the expert review stage, the questions submitted are valid, seen from the results of comments by the validator based on content, construct and language. In the one-to-one stage, two of the three subjects were able to understand the questions well, when analyzing and understanding the PISA type question questions.